Scientific and Methodological Foundations for Studying the Problem of Using Modern Pedagogical Technologies in Education - Abdurashidovna, Dadajanova Dilbar; Khudayberdiyevna, Khudoyberdiyeva Zumrat (Research Parks Publishing LLC, 2022)
This article is devoted to the scientific and methodological foundations for studying the problem of using modern pedagogical technologies in education system, the general features of pedagogical content technologies.